1998
DOI: 10.1093/fampra/15.6.576
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring the primary health care services and changing profile of family physicians in Turkey

Abstract: A new health-reform process has been initiated by Ministry of Health in Turkey. The aim of that reform is to improve the health status of the Turkish population and to provide health care to all citizens in an efficient and equitable manner. The restructuring of the current health system will allow more funds to be allocated to primary and preventive care and will create a managed market for secondary and tertiary care. In this article, we review the current and proposed primary care services models and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…WHO Europe therefore offers support to increase this evidence by means of Biennial Collaborative Agreements (BCAs), which are joint agreements between the respective Ministry of Health and WHO. Turkey started in the mid-90s with a major health care reform restructuring the primary care services offered [10,11]. As a result in 2007, the Ministry of Health in Turkey expressed the wish to support their primary care reforms by implementing the WHO Primary Care Evaluation Tool.…”
Section: Introductionmentioning
confidence: 99%
“…WHO Europe therefore offers support to increase this evidence by means of Biennial Collaborative Agreements (BCAs), which are joint agreements between the respective Ministry of Health and WHO. Turkey started in the mid-90s with a major health care reform restructuring the primary care services offered [10,11]. As a result in 2007, the Ministry of Health in Turkey expressed the wish to support their primary care reforms by implementing the WHO Primary Care Evaluation Tool.…”
Section: Introductionmentioning
confidence: 99%
“…Unadjusted total costs per person were 8% lower in the gate-keeping group. After multivariate adjustment, the estimated cost savings achieved by replacing fee for service based health insurance with gate-keeping in the source population amounted to Sw fr 403-517 (15%-19%) per person (12). In our study, we found that the removal of the gate keeping programme in SII patients has resulted in an increase in cost spent for outpatient visits.…”
Section: Discussionmentioning
confidence: 62%
“…Although the gate-keeping role of the general practitioner was first described in Turkey in the law named Socialization of Health Care (no:224), in 1963 (11), it could not be appropriately applied (12). In Turkey, the gate-keeping system was eliminated in two stages:-in April.…”
Section: Introductionmentioning
confidence: 99%
“…The total numbers of dentists, pharmacists, health officers, nurses, and midwives are 13 421, 18 356, 41461, 69 246, and 41 059 respectively [11]. There are 12.7 physicians per 10 000 inhabitants [12].…”
Section: Manpower In Turkey's Healthcare Services: Approximate Currenmentioning
confidence: 99%